THE ISSUES OF THE INDEPENDENT CURRICULUM IN INDONESIAN LANGUAGE LEARNING AT SMP PGRI DARU, TANGERANG - Nufus, Syakila Hikmatun; Karin, Sholihatunnisa Rizkya; Alyarahmah, Najla (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze various problems that arise in the implementation of the Independent Curriculum in Indonesian language learning at SMP PGRI Daru, Tangerang. This study uses a descriptive qualitative approach that focuses on providing an in-depth depiction of the challenges experienced by teachers and students during the implementation of the Independent Curriculum. The research subjects include Indonesian language teachers who teach grades VII and IX, as they are directly involved in the implementation of the Independent Curriculum at the school. Data collection was conducted through in-depth interviews with teachers as well as documentation, including learning tools and student learning outcome notes. The data obtained were then analyzed through the stages of data reduction, data presentation, and drawing conclusions as outlined in the data analysis model proposed by Miles and Huberman. The results of the study indicate that the transition from the 2013 Curriculum to the Merdeka Curriculum still presents various challenges, particularly in adjusting learning outcomes, preparing teaching modules, and designing a learning objective flow that matches the characteristics of the students. The limitations of learning facilities, especially the limited availability of textbooks, have become the main obstacles in the Indonesian language learning process. Nevertheless, the use of digital devices such as gadgets can serve as an alternative solution in providing additional learning resources for students. From a pedagogical perspective, learning has shown efforts toward being interactive and enjoyable, but the role of the teacher still tends to be dominant, so student engagement has not been fully optimal. In addition, internal factors such as students' interest, attitude, and concentration in learning, as well as external factors like the learning environment, school facilities, and parental support, also influence the success of implementing the Merdeka Curriculum. Therefore, this study recommends improving teacher competence through In-House Training, strengthening the implementation of differentiated learning, and optimizing educational facilities and infrastructure to support the more effective implementation of the Independent Curriculum.